Hazelton Paper - The Production of Gold and Silver in the United States - Rossiter W. Raymond (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The most important event in the history of mining in the United States was the discovery of gold in California, which led to the rapid development, not only of a new industry, but of a new empire. The settlement of the Pacific slope was making but slow progress under the inducements of a scanty commerce in furs and hides. The liberal grants offered by the government to agricultural pioneers in Oregon had attracted to the Willamette valley and other favored points in that territory a limited population; hot the government of the Mexicans in California was positively unfavorable to enterprise. It is true that gold was known to exist in the country. Rumors of it were current among the trappers, and placers had actually been worked in what is now Los Angeles County; but the padres of the neighboring mission of San Fernando had discouraged the business as demoralizing to their flocks; and the existence of the precious metal was not widely known; still less was its distribution northward suspected. The discovery of gold, January 19th) 1848, at Sutter's saw-mill, on the south fork of the American River, afterward famous as Coloma, in Eldorado County, was the beginning of the new epoch. This discovery was made by James Wilson Marshall, a partner in the mill, who observed in the debris washed down by the tail-race a glittering fragment of a mineral unknown to him. Suspecting it to be gold, he sought for further specimens, and obtained, in the course of a few days, several ounces of it. Tests subsequently